The species of cuscus in northern coastal areas of Manokwari, Papua - SEPUS FATEM; DIANA SAWEN (Society for Indonesian Biodiversity, 2007)
This study aims to identify cuscus species found in the northern part areas of Manokwari. The study was conducted on 5-26 November 2005 and 10-25 August 2007. The method used in the research was descriptive by means of applying observation and interview techniques. The result of the research reveals that there are two cuscus species that exist in the area, namely Phalanger orientalis (Mesber) and Spilocuscus maculatus (Mowodu). The activity pattern of cuscus is strongly inter-related to the phases of the moon, weather, and secure and unspoiled environment. The cuscus is commonly hunted by local people for its meat and handicrafts. The local people do not have a pattern of traditional conservations. Therefore, the government needs to issues policies dealing with wildlife hunting.Â© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: Cuscus species, northern area of Manokwari